Connectomic insights into the impact of 1p/19q co-deletion in dominant hemisphere insular glioma patients - Yang, Zuo-cheng; Xue, Bo-wen; Song, Xin-yu; Yin, Chuan-dong; Yeh, Fang-cheng; Li, Gen; Deng, Zheng-hai; Sun, Sheng-jun; Hou, Zong-gang; Xie, Jian (Frontiers in Neuroscience, 2024)
Objectives: This study aimed to elucidate the influences of 1p/19q co-deletion on structural connectivity alterations in patients with dominant hemisphere insular diffuse gliomas.We incorporated 32 cases of left insular gliomas and 20 healthy controls for this study. Using diffusion MRI, we applied correlational tractography, differential tractography, and graph theoretical analysis to explore the potential connectivity associated with 1p/19q co-deletion.The study revealed that the quantitative anisotropy (QA) of key deep medial fiber tracts, including the anterior thalamic radiation, superior thalamic radiation, fornix, and cingulum, had significant negative associations with 1p/19q co-deletion (FDR =4.72×10 -5 ).These tracts are crucial in maintaining the integrity of brain networks. Differential analysis further supported these findings (FWER-corrected p <0.05). The 1p/19q non-co-deletion group exhibited significantly higher clustering coefficients (FDR-corrected p<0.05) and reduced betweenness centrality (FDR-corrected p <0.05) in regions around the tumor compared to HC group. Graph theoretical analysis indicated that non-co-deletion patients had increased local clustering and decreased betweenness centrality in peritumoral brain regions compared to co-deletion patients and healthy controls (FDR-corrected p <0.05).Additionally, despite not being significant through correction, patients with 1p/19q co-deletion exhibited lower trends in weighted average clustering coefficient, transitivity, small worldness, and global efficiency, while showing higher tendencies in weighted path length compared to patients without the co-deletion.The findings of this study underline the significant role of 1p/19q co-deletion in altering structural connectivity in insular glioma patients. These alterations in brain networks could have profound implications for the neural functionality in patients with dominant hemisphere insular gliomas.